Peran Strategis Akuntan dalam Memperkuat Pelaporan Keberlanjutan dan Pelaporan Terintegrasi - Rini Armaya; Tri Ramadhani (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the strategic role of accountants in strengthening sustainability reporting and integrated reporting. A literature review was conducted on relevant articles published between 2021 and 2025 related to accountants and sustainability reporting, ESG, sustainability reporting, integrated reporting, ESG assurance, and the accounting profession. The findings indicate that ESG has become a key framework influencing modern corporate reporting, which requires greater transparency and comparability of non-financial information. The review highlights that accountants play a strategic role not only in preparing reports but also in developing ESG measurement systems, strengthening internal controls, and enhancing the credibility of information through assurance practices. However, the implementation of ESG reporting still faces challenges such as competency gaps, limited technical guidelines, and organizational readiness.